1981
DOI: 10.7164/antibiotics.34.1119
|View full text |Cite
|
Sign up to set email alerts
|

CC-1065(NSC 298223), a potent new antitumor agent. Improved production and isolation, characterization and antitumor activity.

Abstract: CC-1065 (NSC 298223) is a potent new antitumor antibiotic with a unique structure produced by Streptomyces zelensis. Improved production, isolation, and assay methods are described along with physico-chemical properties and antitumor activity. Screening for soil cultures producing agents displaying both cytotoxic activity against L1210 cells in culture and in vivo activity against P388 leukemia in mice afforded a culture, Streptomyces zelensis, producing a new, potent antitumor antibiotic, CC-1065. Its product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 5 publications
1
99
0
Order By: Relevance
“…11) (along with more recent duocarmycin derivatives) is among the most potent antitumor agents discovered to date [86][87][88][89][90][91]. Strictly speaking, CC-1065 is not a QM, but the cyclopropane moiety present on its structure is, from a reactivity point of view, a bioisosteric form of the methide found in QMs.…”
Section: Modulation Of Qm Reactivity Towards Nuc-leophiles Drugs Withmentioning
confidence: 99%
“…11) (along with more recent duocarmycin derivatives) is among the most potent antitumor agents discovered to date [86][87][88][89][90][91]. Strictly speaking, CC-1065 is not a QM, but the cyclopropane moiety present on its structure is, from a reactivity point of view, a bioisosteric form of the methide found in QMs.…”
Section: Modulation Of Qm Reactivity Towards Nuc-leophiles Drugs Withmentioning
confidence: 99%
“…The initial limited studies conducted with naturally derived duo- carmycin SA (3), the most recent addition to this class of agents, revealed a combination of properties that make it the most exciting of the natural products identified to date. In addition to lacking the characteristic of delayed toxicity of ( + )-CCBorn August 22,1953 …”
Section: Reviewsmentioning
confidence: 99%
“…17,18 Studies on the mechanism of cytotoxic action have shown that CC-1065 affords its biological activity through binding to double-stranded B-DNA within the minor groove at AT-rich sequences and selectively alkylating at the N 3 position of the 3'-adenine by its cyclopropylindole (CPI) subunit 12. 19 Despite its high potency and broad spectrum of antitumor activity, CC-1065 cannot be used in humans because it causes delayed death in experimental models.…”
Section: Cpi-distamycin a Hybridsmentioning
confidence: 99%